2021
DOI: 10.1101/2021.09.24.461243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local accessory gene sharing drives lineage-specific acquisition of antimicrobial resistance in Egyptian Campylobacter spp.

Abstract: Campylobacter is the most common cause of bacterial gastroenteritis worldwide and diarrheal disease is a major cause of child morbidity, growth faltering and mortality in low- and middle-income countries (LMICs). Despite evidence of high incidence and differences in disease epidemiology, there is limited genomic data from studies in developing countries. In this study, we characterized the genetic diversity and accessory genome content of a collection of Campylobacter isolates from Cairo, Egypt. In total, 112 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 126 publications
(156 reference statements)
1
1
0
Order By: Relevance
“…Similar trends were observed in published studies ( Ocejo et al, 2019 ; Cobo-Díaz et al, 2021 ; Hailu et al, 2021 ; Hull et al, 2021 ). As previously described ( Ocejo et al, 2019 ; Mouftah et al, 2021 ), blaOXA-193 was the most predominant ARG to beta-lactam compared to other beta-lactamase encoding genes ( blaOXA-449, -461, -603, and 61 ; <10%). However, some other studies have reported blaOXA-61 being predominant in Campylobacter ( Cobo-Díaz et al, 2021 ; Hull et al, 2021 ).…”
Section: Discussionsupporting
confidence: 73%
“…Similar trends were observed in published studies ( Ocejo et al, 2019 ; Cobo-Díaz et al, 2021 ; Hailu et al, 2021 ; Hull et al, 2021 ). As previously described ( Ocejo et al, 2019 ; Mouftah et al, 2021 ), blaOXA-193 was the most predominant ARG to beta-lactam compared to other beta-lactamase encoding genes ( blaOXA-449, -461, -603, and 61 ; <10%). However, some other studies have reported blaOXA-61 being predominant in Campylobacter ( Cobo-Díaz et al, 2021 ; Hull et al, 2021 ).…”
Section: Discussionsupporting
confidence: 73%
“…This observation prompted the formulation of a hypothesis suggesting that C. jejuni isolates from diseased chickens may be more resistant to β-lactams than isolates from diseased ducks and diseased geese. Mouftah et al also found a high prevalence of the bla OXA-605 gene in C. jejuni from broiler carcasses ( 44 ).…”
Section: Discussionmentioning
confidence: 97%